Criminalization in Cases of Unregistered Marriages and Its Impact on the Protection of Women’s Rights - Ainun Yasminnatul Mu’minah (Journal of Human Interaction and Social Studies, 2026)
The practice of unregistered polygamous marriages remains a persistent phenomenon in Indonesia despite the existence of legal provisions regulating the requirements and procedures for polygamy. Such marriages are commonly conducted without official registration and judicial authorization, creating legal uncertainty and potentially undermining the rights of women and children. This study aims to analyze the legal and sociological dynamics of unregistered polygamous marriages and examine the urgency of criminalization as a mechanism for protecting women’s rights. The research employs a normative legal method using statutory and conceptual approaches. Legal materials were obtained through library research, including legislation, legal literature, and relevant scholarly studies. The analysis was conducted qualitatively using Progressive Legal Theory and Utilitarian Theory as analytical frameworks. The findings indicate that unregistered polygamous marriages persist due to interpretations that prioritize the fulfillment of classical Islamic legal requirements while disregarding marriage registration obligations under national law. Marriage registration serves as a crucial instrument for ensuring legal certainty and protecting women’s rights. Criminalization is not intended to prohibit polygamy permitted under Islamic law but to prevent injustice, family neglect, and violations of women’s rights while promoting substantive justice and broader social welfare.